A cross-sectional survey of compliance with national guidance for alcohol consumption by children: measuring risk factors, protective factors and social norms for excessive and unsupervised drinking - Bellis Mark A; Morleo Michela; Hughes Karen; Downing Jennifer; Wood Sara; Smallthwaite Linda; Cook Penny A (BMC, 2010)
Abstract Background The Chief Medical Officer for England has developed the first guidance in England and some of the first internationally on alcohol consumption by children. Using the most recent iteration of a large biennial survey of schoolchildren we measure the extent to which young people's drinking fell within the guidelines just prior to their introduction and the characteristics of individuals whose drinking does not; how alcohol related harms relate to compliance; and risk factors associated with behaving outside of the guidance. Methods A cross-sectional survey was conducted utilising a self-completed questionnaire with closed questions. A total of 11,879 schoolchildren, aged 15-16 years, from secondary schools in North West England participated in the study. Data were analysed using chi square and conditional logistic regression. Results Alcohol consumption is an established norm by age 15 years (81.3%). Acute alcohol related violence, regretted sex and forgetfulness were experienced by significantly fewer children drinking within the guidance (than outside of it). Over half of drinkers (54.7%) reported routinely drinking more heavily than guidance suggests (here ≥5 drinks/session ≥1 month), or typically drinking unsupervised at home or at a friend's home when parents were absent (57.4%). Both behaviours were common across all deprivation strata. Children with greater expendable incomes were less likely to consume within guidance and reported higher measures for unsupervised, frequent and heavy drinking. Although drinking due to peer pressure was associated with some measures of unsupervised drinking, those reporting that they drank out of boredom were more likely to report risk-related drinking behaviours outside of the guidance. Conclusions Successful implementation of guidance on alcohol consumption for children could result in substantial reductions in existing levels of alcohol related harms to young people. However, prolonged social marketing, educational and parental interventions will be required to challenge established social norms in heavy and unsupervised child drinking across all social strata. Policy measures to establish a minimum price for alcohol and provide children with entertaining alternatives to alcohol should also increase compliance with guidance.